Revisiting I/O Behavior in Large-Scale Storage Systems: The Expected and the Unexpected - Patel, Tirthak; Byna, Suren; Lockwood, Glenn K.; Tiwari, Devesh (SC19: International Conference for High Performance Computing, Networking, Storage and Analysis, 2019)
Large-scale applications typically spend a large fraction of their execution time performing I/O to a parallel storage system. How-ever, with rapid progress in compute and storage system stack of large-scale systems, it is critical to investigate and update our understanding of the I/O behavior of large-scale applications. Toward that end, in this work, we monitor, collect and analyze a year worth of storage system data from a large-scale production parallel stor-age system. We perform temporal, spatial and correlative analysis of the system and uncover surprising patterns which defy existing assumptions and have important implications for future systems.